Use of Karl Fischer titration for the localized measurement of water content in FRP composite aircraft parts removed from service. (April 2023) - Gillet, Camille; Splawski, Wilfried; Aguirre, Florian; Hassoune-Rhabbour, Bouchra; Tchalla, Tatiana; Nassiet, Valérie
Moisture content measurements are performed on scrapped Outlet Guide Vanes (OGV) that have operated in different climates. These measurements are made by three Karl Fischer titration methods. The results are separated into two parts. On one side, a comparison of these different techniques highlights their advantages and disadvantages. The methods for studying the samples and the duration of the tests differ. The standard method is not sufficient to extract all the water from the samples. The chemical extraction and grinding methods provide higher water content. On the other side, a mapping of the water content through three scrapped OGV blades is performed with the Karl Fischer titration. Differences are observed according to the service area climate. Concentration gradients are also visible within the part, with more water at the leading edges and less water in the foam. Parts that have flown in hot and humid regions have the lowest water contents by standard Karl Fischer titration. These measurements are compared with the analysis of the damage they have been subjected to. They allow to highlight the composite material degradation, manifested by resin erosion, which is more significant for parts that have operated in wet and humid areas. This erosion involves a lower resin percentage and could explain the lower water contents measured.